Relationship between the elasticity of polymeric gels and the in-vitro release of medicament / Sharifah Fatimatuzzahrah Abdullah Alshatri - Abdullah Alshatri, Sharifah Fatimatuzzahrah (2014)
Gels are semi solid dosage form that comprise small amount of solid and dispersed in relatively with large amount of liquid, but still having solid-like character. Rheological properties of gels may affect the release of medicament from it. Elasticity of gel may affect the release of medicament from it. The objective of this study is to find the relationship between the elasticity of polymeric gels and the in-vitro release of medicament from them. Five types of gels bases were prepared to observe their rheological properties and the release of medicament after the gels incorporated with medicament. Type of gel bases that were prepared are glycerin of starch gel, gelatin-glycerin gel, sodium carboxy methyl cellulose gel, carbopol 934 gel and Eudragit L 100 gel. Rheological properties of gels were observed by using Rheometer. Whereas, all five medicated gels were subjected to analysis by Franz diffusion cell method to study the in-vitro release of medicament from the gels and the sample of from the test was analyzed by UV spectrophotometric to obtain the concentration of Ketoconazole release. Relationship between the elasticity of gel and the release of medicament was observed. The result was showed that the higher the elasticity of gel the higher the release of medicament.